18 Month Old Male with Incomplete Kawasaki Disease - Paul Roszko; Frank Overly (Association of American Medical Colleges, 2013)
Abstract There are 3,000 to 5,000 cases of Kawasaki disease per year in the United States, the vast majority of which occur in children under the age of five. Although as traditionally taught, Kawasaki disease presents with a fever of greater than 5 days and four of five clinical criteria, physician's must be aware of cases of incomplete Kawasaki disease. The clinical consequences and treatment of both presentations are similar, and this case helps to strengthen and broaden a physician's differential diagnosis of fever of greater than 5 days without a clear explanation. This case is designed to help remind emergency physicians and pediatricians on the various ways that Kawasaki disease may present, including the classic and incomplete patterns. This high-fidelity simulation case features an 18-month-old male who presents to a pediatric emergency department with several days of fever and a rash. The case contains a PowerPoint presentation intended to be used as a debriefing of the case and to review the key component of Kawasaki disease and Incomplete Kawasaki disease, as well as the main differential diagnosis of a pediatric patient with fever and a rash. The case targets pediatric or emergency medicine residents or fellows. This case was created and used during a simulation session for the Brown University Emergency Medicine program to aid residents and fellows in their clinical decision-making and treatment of patients with fever and a rash. After completion of the simulation, the case has since been modified and updated based on participant feedback.